Offering research education for in-service language teachers. (14th March 2017) - Bardel, Camilla; Erickson, Gudrun; Granfeldt, Jonas; Rosén, Christina
Abstract : Since 2008, the Swedish government has launched occasional offers of funding for graduate schools aimed at practising teachers. The fundamental purpose of this initiative is to enhance quality in the Swedish school system by implementing what is stated in the Education Act, namely that education at all levels should be based upon scientific knowledge and evidence-based experience.